"untitled" - Zamora Cascante, Diego (2018)
The brief history of Costa Rican art presents significant milestones for the understanding of what we know today as artistic production. The First Central American Painting Biennial was a milestone not only for the country, but also for the region, due to the jury's decisions and the strong criticism of the participating artists. Thanks to this fact, the contemporary artistic work is contrasted with its beginnings taking as a reference the year of 1971 to look back and become aware of what we find today in the galleries and museums. This essay explores this.